Marker Assisted Gene Pyramiding (MAGP) for bacterial blight and blast resistance into mega rice variety “Tellahamsa” - Jamaloddin, Md.; Durga Rani, Ch. V.; Swathi, G.; Anuradha, Ch.; Vanisri, S.; Rajan, C. P. D.; Krishnam Raju, S.; Bhuvaneshwari, V.; Jagadeeswar, R.; Laha, G.S.; Prasad, M.S.; Satyanarayana, P.V.; et al. (Public Library of Science, 2020)
Bacterial blight (BB) and fungal blast diseases are the major biotic constraints that limit rice productivity. To sustain yield improvement in rice, it is necessary to developed yield potential of the rice varieties by incorporation of biotic stress resistance genes. Tellahamsa is a well-adapted popular high yielding rice variety in Telangana state, India. However, the variety is highly susceptible to BB and blast. In this study, simultaneous stepwise transfer of genes through marker-assisted backcross breeding (MABB) strategy was used to introgress two major BB (Xa21 and xa13) and two major blast resistance genes (Pi54 and Pi1) into Tellahamsa. In each generation (from F1 to ICF3) foreground selection was done using gene-specific markers viz., pTA248 (Xa21), xa13prom (xa13), Pi54MAS (Pi54) and RM224 (Pi1). Two independent BC2F1 lines of Tellahamsa/ISM (Cross-I) and Tellahamsa/NLR145 (Cross-II) possessing 92% and 94% recurrent parent genome (RPG) respectively were intercrossed to develop ICF1—ICF3 generations. These gene pyramided lines were evaluated for key agro-morphological traits, quality, and resistance against blast at three different hotspot locations as well as BB at two locations. Two ICF3 gene pyramided lines viz., TH-625-159 and TH-625-491 possessing four genes exhibited a high level of resistance to BB and blast. In the future, these improved Tellahamsa lines could be developed as mega varieties for different agro-climatic zones and also as potential donors for different pre-breeding rice research.